IPCA: an integration information system for patient controlled analgesia using wireless techniques. (22nd May 2013) - Yang, Shu–Fen; Ku, Tien–Hsiung; Jeng, Andy An–Kai; Jan, Rong–Hong; Tseng, Yu–Chee; Wang, Kuo–Chen; Hu, Yuh–Jyh
Recently, pain management has become an important aspect of medical care. Patient Controlled Analgesia (PCA) is a particularly effective and flexible treatment that allows patients to adjust the dosages of the analgesics that control their pain after surgery. However, PCA requires manual operation for sustained attention, and should be analysed with other pathology information for synergic usage. In this paper, we propose an integrated information system for pain management, called Integrated Patient Controlled Analgesia (iPCA). The system integrates various PCA–related devices by wireless techniques to provide real–time information for medial staffs, and offer more efficient and convenient pain control for both in–hospital and at–home patients. To evaluate our system, we have developed a prototype and conducted a series of field trails at a large private hospital in southern Taiwan. The results show that the iPCA system indeed works well with patients, and can provide better post–operative pain control by efficiently collecting PCA usage information.